Traditional Chinese medicine prescription Shenling BaiZhu powder to treat ulcerative colitis: Clinical evidence and potential mechanisms - Chen, Jing; Shen, Bixin; Jiang, Zhengli (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC), characterized by syndromes including abdominal pain, bloody stool, diarrhea, weight loss, and repeated relapse, is a non-specific inflammatory intestinal disease. In recent years, with the changing dietary habits in China, the incidence of UC has shown an upward trend. UC belongs to the category of recorded as “diarrhea,” “chronic dysentery,” and “hematochezia” in traditional Chinese medicine (TCM), and Shenling BaiZhu powder (SLBZP) is one of the most effective and commonly used prescriptions. In this review, we aim to systematically summarize the clinical application and pharmacological mechanism of SLBZP in the treatment of UC to provide a theoretical basis for its clinical use and experimental evaluation of SLBZP. Our results showed that both SLBZP and SLBZP in combination with chemical drugs, have a significant therapeutic effect against UC with few adverse reactions. Furthermore, combined therapy was better than western medicine. Further, pathophysiological studies indicated that SLBZP has anti-inflammatory, immunomodulatory, antioxidant effects, regulation relative cell signal transduction and regulation of gut microbiota. Although evidence suggests superior therapeutic efficacy of SLBZP for treating UC and the relative mechanism has been studied extensively, various shortcomings limit the existing research on the topic. There is a lack of UC animal models, especially UC with TCM syndromes, with no uniform standard and certain differences between the animal model and clinical syndrome. The dosage, dosage form, and therapeutic time of SLBZP are inconsistent and lack pharmacological verification, and clinical trial data are not detailed or sufficiently rigorous. In addition, SLSZP is composed of multiple Chinese drugs that contain massive numbers of ingredients and which or several components contribute to therapeutic effects. How they work synergistically together remains unknown. Therefore, on the one hand, large sample prospective cohort studies to clarify the clinical efficacy and safety of SLBZP in the treatment of UC are needed. In contrast, researchers should strengthen the study of the molecular biological mechanism of active ingredients and its synergistic actions, clarifying the mechanism of SLBZP in treating UC by multi-component, multi-target, and multi-pathway.